2019
DOI: 10.1038/s41467-019-10278-x
|View full text |Cite|
|
Sign up to set email alerts
|

Tau binding protein CAPON induces tau aggregation and neurodegeneration

Abstract: To understand the molecular processes that link Aβ amyloidosis, tauopathy and neurodegeneration, we screened for tau-interacting proteins by immunoprecipitation/LC-MS. We identified the carboxy-terminal PDZ ligand of nNOS (CAPON) as a novel tau-binding protein. CAPON is an adaptor protein of neuronal nitric oxide synthase (nNOS), and activated by the N-methyl-D-aspartate receptor. We observed accumulation of CAPON in the hippocampal pyramidal cell layer in the App NL-G-F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 60 publications
(84 reference statements)
9
62
0
Order By: Relevance
“…In the present study, astaxanthin supplementation to the experimental mice started from 5-to-6 weeks old before Ab deposition started, and the mice were sacrificed at 9 months old so that the protective effects of astaxanthin on the onset and progression of AD could be analyzed. In this model, we observed mild memory decline, accumulation of Ab42 in the hippocampus and PFC, a mild increase in pTau fraction, and microglial accumulation (an increase in Iba1 fraction) in the App NL-G-F mice, which is consistent with the previous studies (Saito et al, 2014;Masuda et al, 2016;Hashimoto et al, 2019). These deficits in memory functions may not be ascribed to confounding effects outside the brain such as deficits in visual acuity and locomotor activity in the App NL-G-F mice since a previous study reported that motor and visual capabilities of App NL-G-F and WT mice were comparable at 24 months old (Sakakibara et al, 2019).…”
Section: Pathology In the Mouse Ad Modelsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, astaxanthin supplementation to the experimental mice started from 5-to-6 weeks old before Ab deposition started, and the mice were sacrificed at 9 months old so that the protective effects of astaxanthin on the onset and progression of AD could be analyzed. In this model, we observed mild memory decline, accumulation of Ab42 in the hippocampus and PFC, a mild increase in pTau fraction, and microglial accumulation (an increase in Iba1 fraction) in the App NL-G-F mice, which is consistent with the previous studies (Saito et al, 2014;Masuda et al, 2016;Hashimoto et al, 2019). These deficits in memory functions may not be ascribed to confounding effects outside the brain such as deficits in visual acuity and locomotor activity in the App NL-G-F mice since a previous study reported that motor and visual capabilities of App NL-G-F and WT mice were comparable at 24 months old (Sakakibara et al, 2019).…”
Section: Pathology In the Mouse Ad Modelsupporting
confidence: 92%
“…The correlational analyses indicated that Ab42 fraction was positively correlated with pTau and Iba1 fraction, while memory functions (number of visits to the goal region) were negatively correlated with Ab and pTau fractions. These findings in this mouse AD model represent characteristics of human AD pathological findings and support the amyloid cascade theory of AD, in which accumulation of pathogenic Ab induces amyloid plaques, hyperphosphorylation of tau (tauopathy), and microglial activation (Hardy and Selkoe, 2002;Selkoe and Hardy, 2016;Sasaguri et al, 2017;Edwards, 2019;Hashimoto et al, 2019).…”
Section: Pathology In the Mouse Ad Modelsupporting
confidence: 79%
See 2 more Smart Citations
“…Several tau mouse models that recapitulate pathological features of tauopathy have been developed with mutations in the MAPT gene, including P301S [13], P301L (rTg4510 under CaMKII [14], prion [15] and Thy1.2 [16] promotors), and hTau lines [17]. Whole brain highresolution tau imaging in these disease models provide insights for mechanistic and therapeutic studies [18,19].…”
Section: Introductionmentioning
confidence: 99%